2011
DOI: 10.1007/s12070-010-0094-5
|View full text |Cite
|
Sign up to set email alerts
|

Ligation Versus Bipolar Diathermy for Hemostasis in Tonsillectomy: A Comparative Study

Abstract: Tonsillectomy despite being less performed nowadays still is a very common surgery performed by ENT surgeons. The use of various modalities like bipolar diathermy, laser, cryosurgery, radiofrequency and ionic coblation for hemostasis in tonsillectomy remains controversial so far. A thorough scan of literature comparing the ligation with diathermy has been presented. In this prospective study, we analysed 50 patients undergoing tonsillectomy by dissection method. Right sided tonsillectomies act as study group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…In study conducted by P.K.Moonka 2 he found bipolar diathermy is not significantly more painful post operatively as ligation. In study conducted by Karan Sharma 5 there was comparable postoperative pain in bipolar diathermy & ligation methods. * In our study, in Electrocautery group 2 patients (4%) had postoperative vomiting, whereas in Ligation group 3 patients (6%) patients had postoperative vomiting.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In study conducted by P.K.Moonka 2 he found bipolar diathermy is not significantly more painful post operatively as ligation. In study conducted by Karan Sharma 5 there was comparable postoperative pain in bipolar diathermy & ligation methods. * In our study, in Electrocautery group 2 patients (4%) had postoperative vomiting, whereas in Ligation group 3 patients (6%) patients had postoperative vomiting.…”
Section: Discussionmentioning
confidence: 92%
“…The study conducted by Zeeshan Ayub 4 showed monopolar diathermy as a better method for haemorrhage control as compared to silk ligatures. In study conducted by Karan Sharma 5 he found average blood loss was remarkably reduced while using bipolar diathermy as compared to ligation. * In our study, average duration taken for tonsillectomy operation where cautery was used as method of haemostasis was 27 minutes whereas duration taken for tonsillectomy operation using ligation as method of haemostasis is 29.5 minutes.…”
Section: Discussionmentioning
confidence: 97%
“…(1) The main indications for to nsill ecto my are sleep disorder breathing due to enlarged to nsil sand sore throat due to recurrent throat infections. (2) An ideal tonsillectomy operation should have little or no morbidity and mortality , easily available and cost effective with out surgical complications if possible.…”
Section: Introductionmentioning
confidence: 99%
“…Painless surgery remains a great aimand should allow a more early back return to normal diet and daily activity with excellent outcome. (3) Post tonsillectomy pain is a problem that the magnitudeof pain in the postoperative period varies as it may be more intense in early morning and reduces during the rest of the day with analgesic medication andkeeping throat moist by cold fluidbut sometimes pain worsens again in the evening, especially during the first three days with swallowing (4) Referred otalgiawith swallowing usually occurred due to common 9 th sensory nerve innervation for both ear and throat that is relieved with regular doses of pain control given every 4 to 6 hours especially in the first 2 to 3 days.. (5) Conventional dissection technique for tonsillectomy operation had the advantage that it is a safe procedure with fewer incidence for post operative complications as bleeding with the possibility for the tonsil can be removed in toto without any remnants and remained the standard procedure for tonsillectomy for many years till now (6) CO 2 Laser tonsillectomy is done with wavelength of 10.6 2 micron is at the peak of absorption of water. This is important to concentrate the energy with little heat to dissipate to adjacent tissues and minimal damage to surrounding structures with minimal edema that focused to create a precise cut and defocused to produce coagulation of small blood vessels so it Fahd Ali Alharbi and Mohamed Rifaat Ahmed: Postoperative Pain After Tonsillectomy; Comparison Between CO 2 Laser Versus Conventional Dissection Tonsillectomy gives clear bloodless field during surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation